2021
DOI: 10.3390/nano11092384
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Serum Protein Biomarkers of Non-Muscle Invasive Bladder Cancer after Protein Corona-Silver Nanoparticles Analysis by SWATH-MS

Abstract: Because cystoscopy is expensive and invasive, a new method of detecting non-invasive muscular bladder cancer (NMIBC) is needed. This study aims to identify potential serum protein markers for NMIBC to improve diagnosis and to find treatment approaches that avoid disease progression to a life-threatening phenotype (muscle-invasive bladder cancer, MIBC). Here, silver nanoparticles (AgNPs, 9.73 ± 1.70 nm) as a scavenging device together with sequential window acquisition of all theoretical mass spectra (SWATH-MS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Similarly, using a comparable approach, the biomarkers S100A8 and S100A4 accurately (ROC, 0.941) distinguished 92% of low-grade cases from high-grade ones, with the utmost levels of sensitivity and specificity [ 25 ]. Another study by Gómez et al used serum samples to compare two NMIBC subtypes, T1 and Ta, with normal samples using the SWATH-MS technique and identified 40 differentially expressed proteins [ 26 ]. Important altered proteins implicated in the complement and coagulation cascade pathways and apolipoproteins include Galectin-3-binding protein (LGALS3BP), Alpha-1-antitrypsin (SERPINA1), Alpha-1-antichymotrypsin (SERPINA3), Apolipoprotein A-II (APOA2), Hemoglobin subunit beta (HBB), and Apolipoprotein F (APOF) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, using a comparable approach, the biomarkers S100A8 and S100A4 accurately (ROC, 0.941) distinguished 92% of low-grade cases from high-grade ones, with the utmost levels of sensitivity and specificity [ 25 ]. Another study by Gómez et al used serum samples to compare two NMIBC subtypes, T1 and Ta, with normal samples using the SWATH-MS technique and identified 40 differentially expressed proteins [ 26 ]. Important altered proteins implicated in the complement and coagulation cascade pathways and apolipoproteins include Galectin-3-binding protein (LGALS3BP), Alpha-1-antitrypsin (SERPINA1), Alpha-1-antichymotrypsin (SERPINA3), Apolipoprotein A-II (APOA2), Hemoglobin subunit beta (HBB), and Apolipoprotein F (APOF) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Garcia-Bennett et al 81 have found that nanodiamonds formed similar protein coronas despite the presence of different surface groups. Goḿez et al 82 identified potential serum protein markers of cancer patients on AgNPs together with SWATH-MS for improved diagnosis.…”
Section: Analytical Techniques For Probing the Protein Coronamentioning
confidence: 99%
“…Concerns are growing about how to accurately distinguish between different subtypes of bladder cancer. To investigate this problem, Gómez et al (2021) performed SWATH‐MS to detect changes in serum proteins of patients with two nonmuscular invasive bladder cancer (NMIBC) subtypes, T1 and Ta, and compared the results with samples of the healthy people. They identified 16 proteins specifically associated with the T1 subtype and 22 proteins specifically associated with the Ta subtype and suggested that these proteins are candidate prognostic biomarkers for NMIBC.…”
Section: Application Of the Lfq Proteomics Technology For Malignant T...mentioning
confidence: 99%